Neue Hiastatus-Arten (Diptera: Itonididae). - Mamajev, Boris M. (Contributions to Entomology = Beiträge zur Entomologie, 1961)
Four new species of the genus Hiastatus Marikovskij are described. The larvae of H. xylophilus n. sp. develop unter decayed bark (Caucasia). Other species were collected in the Moskov district. Their biology is still unknown. The species may easily be distinguished by means of the morphologic characters of the hypopygium. Nomenclatural Actsabnormis Mamajev, 1961 (Hiastatus), spec. n.curvidentatus Mamajev, 1961 (Hiastatus), spec. n.marikovskii Mamajev, 1961 (Hiastatus), spec. n.xylophilus Mamajev, 1961 (Hiastatus), spec. n.